A Conceptual Review of the Effectiveness of Limonia Acidissima Decoction in Vitiligo Management (International Journal of Ayurveda and Pharma Research, 2024)
Limonia acidissima also known as wood apple is a wild-growing medicinal plant distributed throughout India and Sri Lanka. Traditional practitioners in Sri Lanka, along with those using folk medicine and Ayurvedic toxicology principles, have reported that different extracts of Limonia acidissima are effective in managing vitiligo. Further research using advanced techniques is required to scientifically validate Ayurvedic and traditional medicines, yet there is limited emphasis on clinical studies and a deeper understanding of the specific properties of Limonia acidissima. This study aims to review and integrate current information on the pharmacological features of Limonia acidissima decoction component and assess its efficiency in treating vitiligo. Authentic Ayurvedic scriptures, modern writings, and previous research projects were used to gather information regarding Limonia acidissima. This study identified for various pharmacological properties, according to the Ayurveda, Vishagna (antitoxic), Shotha (anti-inflammatory), Yakrut Uttejaka (hepato-protective) along with its immune-modulatory, anti-oxidant, anti-inflammatory, regulation of cytokines and its potential utility in vitiligo treatment. Bioactive compounds present in wood apple contribute to its antioxidant functions. These are indirectly support vitiligo treatment and its application specifically to vitiligo is not well-established in direct clinical research. Limonia acidissima is used in traditional and folk medicine to treat vitiligo, a condition with white spots. However, there is a lack of scientific proof in clinical settings, mechanisms of action, including, autoimmune response regulation, melanogenesis enhancement, and interaction with other vitiligo-related signaling pathways. Therefore, clinical, immunological, and analytical research could provide valuable information for vitiligo treatment.